Effect of yolk and sugar levels in dilutors on motility of buffalo spermatozoa during refrigeration preservation - KUMAR, SATISH; SAHNI, K L; MOHAN, GREESH (The Indian Journal of Animal Sciences, 2013)
Murrah buffalo semen (initial motility 70% and above) was preserved at SoC up to 72 hr in milk, tris and sodium citrate dilutors with different levels of yolk and different concentrations of various sugars and no glycerol. Motility in all the buffers varied in the presence of different yolk levels. Highest motility with 5% yolk was ohserved and it decreased as yolk concentration increased. During the first 24 hr of preservation tris was better overmilk and citrate, but on subsequent hours of preservation milk was better and citrate was poorest among all the 3 buffers. Addition of sugars increased the motility in milk and tris but not in citrate. Different sugars behaved differently in different buffers and lower level of sugars were slightly beneficial over its higher level. During refrigeration storage, concentration of yolk and type and levels of sugars are important factors in determining the preservation protection.